How Do Companies Communicate Sustainability: A Semantic Analysis of German Automotive Manufacturers - Fabienne Le (Junior Management Science (JUMS), 2024)
CSR is increasingly becoming an integral part of a company's business operation. To successfully implement a CSR strategy, companies must address their CSR actions to their stakeholders. This paper examines how companies communicate sus- tainability to their stakeholders through various communication channels. This paper supports the novel strand of research applying computer-aided quantitative analysis methods as an alternative to qualitative methods, commonly used in business ethics and sustainability research. With the application of a latent semantic analysis, four automotive companies were exam- ined for their sustainability communication. The paper offers new insights into the use of different communication channels, highlighting that companies address specific aspects of their CSR actions depending on what stakeholder group they want to address.
Keywords: 650; communication channels; computer-aided quantitative analysis; CSR; latent semantic analysis; sustainability; triple bottom line